Constructive Side-Channel Analysis and Secure Design: 12th International Workshop, COSADE 2021, Lugano, Switzerland, October 25-27, 2021, Proceedings - Bhasin, Shivam; De Santis, Fabrizio (Lecture Notes in Computer Science, 2021)
This book constitutes revised selected papers from the 11th International Workshop on Constructive Side-Channel Analysis and Secure Design, COSADE 2021, held in Lugano, Switzerland, in October 2021.The 14 full papers carefully reviewed and selected from 31 submissions are presented in this volume together with the 4 extended keynote abstracts. The workshop covers the following subjects: cryptography, side-channel analysis, cryptographic implementations, fault attacks, implementation attacks, post-quantum cryptography, hardware accelerators, etc.